If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2a + -1b = 1 Solving 2a + -1b = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. 2a + -1b + b = 1 + b Combine like terms: -1b + b = 0 2a + 0 = 1 + b 2a = 1 + b Divide each side by '2'. a = 0.5 + 0.5b Simplifying a = 0.5 + 0.5b

| 4(6x+5)=10 | | 5(4y-1)=47 | | 5(2k+3)=36 | | -4+2x=12 | | -4+2x=0 | | 5(3x+8)=30 | | 9x-5=7x+5 | | 6x+38=16x-62 | | 5x-3=15x-43 | | 1+9x=57+x | | 6x-x+9=19 | | 6x-x+9=19 | | X-2y=10 | | -20+4x=0 | | 7y+5=-9 | | 5k-(-7)=-7 | | -5b-12=-2 | | 9f+15=51 | | x+3(x+2)=30 | | 11a-9+5a+26= | | 2(m+7)=4(11-m) | | 5+13x=31 | | x+x+2+x+4=345 | | f-32=1.8c | | 5+13x=70 | | p+31=29 | | x-6x+11+3x+4x-4=13+2.4 | | 5y+3=4y-6 | | 3x+4=40 | | 9-6y=3-7y | | 24+3z=99 | | 5(x+1)-4(x-1)=0 | | (14x^5)(6x^4)= | | 2-4x=-18 | | 2(4x+8)=-45+13 | | 6x+5=23 | | 2x+8= | | 3x+2=2(x-6)+5 | | 7x+8=78 | | -7+6x=-13 | | -4x-5= | | 6x+4=28 | | 7x+9=93 | | -6x-4-2x=36 | | 9-3x-3x=45 | | 8x+4+x= | | 4x-7x=7 | | 15+6z=81 | | 1+4X+23= | | 4y+4=28 | | x+8=-x+6+2x | | 3(x-4)=40 | | -8-3x=-11 | | 4x+4+4x=92 | | 4x+1=2x+12 | | -6x-5-2x=-21 | | -7=-7x+2x+3 | | x-4=-11 | | 4+x+4x=-21 | | 2x-x^2=9 | | 3(5x-2)=2(4x+11) | | 4(x-4)=40 | | 0.5x-5=x+4 | | 49=6x-2x+5 | | 4(x+4)=40 |